The spatial structure of the dayside ionospheric trough - S. E. Pryse; L. Kersley; M. J. Williams; I. K. Walker (Annales Geophysicae, 1998)
Tomographic imaging provides a powerful technique for obtaining images of the spatial distribution of ionospheric electron density at polar latitudes. The method, which involves monitoring radio transmissions from the Navy Navigation Satellite System at a meridional chain of ground receivers, has particular potential for complementing temporal measurements by other observing techniques such as the EISCAT incoherent-scatter radar facility. Tomographic reconstructions are presented here from a two-week campaign in November 1995 that show large-scale structuring of the polar ionosphere. Measurements by the EISCAT radar confirm the authenticity of the technique and provide additional information of the plasma electron and ion temperatures. The dayside trough, persistently observed at high latitudes during a geomagnetically quiet period but migrating to lower latitudes with increasing activity, is discussed in relationship to the pattern of the polar-cap convection. Key words. Ionosphere-magnetosphere interactions · Polar ionosphere · Radio science · Ionospheric propagation